Robot-assisted laparoscopic pyeloplasty for ureteropelvic junction obstruction with duplex system - Numakura, Kazuyuki (Urol Case Rep, 2020)
Management of ureteropelvic junction obstruction with a duplex system is technically challenging even when laparoscopic procedure is the standard approach for ureteropelvic junction obstruction. The patient was an otherwise healthy 21-year-old woman who presented with symptomatic ureteropelvic junction obstruction with the duplex system, which was completely excised using a robot-assisted approach. Robotic assistance allows for proper tissue dissection, minimal manipulation of the normal ureter, and meticulous fine suturing and would overcome the potential challenges involved in the minimally invasive management of such complex anomalies as shown in this patient.